A Need Assessment for Faculty Development in Baccalaureate Nursing Programs in Pakistan (International Journal of Studies in Nursing, 2018)
Objective: A needs assessment was undertaken for faculty development needs of nurse educators teaching in baccalaureate nursing education programs across Pakistan. Methodology: The survey instrument was developed by the researcher in consultation with an advisory committee. It contained 25 items that reflected the demographic profile of the participants and another 98 statements on a 5 point Likert type scale to assess faculty development. Data collection was done across twenty schools of nursing. Results: The major findings of the study indicated a critical shortage of academically prepared nursing faculty with advanced degrees and teaching experience to perform their role effectively. Female faculty outnumbered male faculty. Five factors were identified that could both promote or obstruct faculty development and included awareness and convenience, institutional support, prevailing leadership, politics and personal factors. Additionally, four factors were extracted for challenges for undertaking faculty development; technology and curriculum, students and resources, academic leadership and professional role. Lastly, four factors were identified as areas of interests for faculty development; learning and instruction, support for scholars, support for teaching and national curriculum. Conclusion: This is the first national needs assessment that has been undertaken for faculty development for baccalaureate nursing programs in Pakistan. Although, the data may not hold international significance it would add to the existing international data base on needs assessment for faculty development.